ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR PADA SISWA KELAS IX SMP DI KOTA CIMAHI - Khoirul Bariyyah; Risma Amelia (IKIP Siliwangi, 2020)
This study aims to describe the mistakes made by students of grade IX Middle School. As well as analyzing the factors that cause students to mistake in completing the material on flat side spaces in junior high school students in Cimahi City. The method used in this research is descriptive qualitative. The sample taken for this study was 10 students of class IX in one junior high school in Cimahi City. The test instrument was given as many as 5 items. Based on the results of data analysis, it can be concluded that there are errors in solving the problem of getting up the flat side space, namely: (1) not understanding the basic concept of building a flat side space; (2) lack of understanding of questions or lack of thoroughness in reading problems so students' answers are incomplete; (3) lack of mastery of the principle or conceptual relationship between flat figures (prerequisites regarding the Pythagorean theorem); (4) don't memorize the formula; (5) lack of precision in the calculation process. And this shows that grade IX students in Cimahi City are still low in solving problems in the material to build flat side spaces.